2022
DOI: 10.1002/ijc.34223
|View full text |Cite
|
Sign up to set email alerts
|

Identification of prediagnostic metabolites associated with prostate cancer risk by untargeted mass spectrometry‐based metabolomics: A case‐control study nested in the Northern Sweden Health and Disease Study

Abstract: Prostate cancer (PCa) is the most common cancer form in males in many European and American countries, but there are still open questions regarding its etiology.Untargeted metabolomics can produce an unbiased global metabolic profile, with the opportunity for uncovering new plasma metabolites prospectively associated with risk of PCa, providing insights into disease etiology. We conducted a prospective untargeted liquid chromatography-mass spectrometry (LC-MS) metabolomics analysis using prediagnostic fasting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…However, several research from Heidelberg ( 14 ), Baltimore ( 13 ) and European-based Mendelian randomization ( 16 ) concluded that there was no relationship between SUA and the incidence of prostate cancer. Additionally, studies utilizing populations from Sweden ( 22 ), Japan ( 8 , 23 ), and Korea ( 12 ) revealed a positive association between SUA and prostate cancer. The following explanations might account for this contradicting outcome.…”
Section: Discussionmentioning
confidence: 99%
“…However, several research from Heidelberg ( 14 ), Baltimore ( 13 ) and European-based Mendelian randomization ( 16 ) concluded that there was no relationship between SUA and the incidence of prostate cancer. Additionally, studies utilizing populations from Sweden ( 22 ), Japan ( 8 , 23 ), and Korea ( 12 ) revealed a positive association between SUA and prostate cancer. The following explanations might account for this contradicting outcome.…”
Section: Discussionmentioning
confidence: 99%